2021
DOI: 10.1002/fft2.71
|View full text |Cite
|
Sign up to set email alerts
|

Functional foods with dipeptidyl peptidase‐4 inhibitory potential and management of type 2 diabetes: A review

Abstract: The global high prevalence of diabetes mellitus has resulted into the development of several oral hypoglycemic agents. However, these drugs have limited efficacy and harmful side effects, which call for the search for alternatives from natural sources. The inhibition of dipeptidyl peptidase‐4 (DPP‐4) activity increases the level of glucagon‐like peptide‐1 and glucose‐dependent insulinotropic polypeptide, which in turn reduces hyperglycemia by activating insulin secretion and inhibiting glucagon secretion. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Type II diabetes (T2D) is a common chronic disease. It accounts for 90%–95% cases of diabetes mellitus, a relatively common metabolic syndrome which is accompanied by certain complex complications including generalized brain atrophy, greater high-intensity lesion volumes, hippocampal, and amygdala atrophy ( Kazeem et al, 2021 , Lee et al, 2012 , Zhao et al, 2020 ). Typically, this disease is known to occur in older adults, and the number of aging-related diabetic (AD) patients progressively increases owing to aging of the islet β-cells ( Atella et al, 2019 , Fuster et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Type II diabetes (T2D) is a common chronic disease. It accounts for 90%–95% cases of diabetes mellitus, a relatively common metabolic syndrome which is accompanied by certain complex complications including generalized brain atrophy, greater high-intensity lesion volumes, hippocampal, and amygdala atrophy ( Kazeem et al, 2021 , Lee et al, 2012 , Zhao et al, 2020 ). Typically, this disease is known to occur in older adults, and the number of aging-related diabetic (AD) patients progressively increases owing to aging of the islet β-cells ( Atella et al, 2019 , Fuster et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In reaction to consumed foods, the gut releases hormones known as incretins. These hormones result in a glucose-induced insulin response ( Kazeem et al, 2021 ). They are secreted by intestinal endocrine L-cells and K-cells.…”
Section: Construction and Application Of Intestinal Organoidsmentioning
confidence: 99%
“…Vitexin exhibited a greater half-maximal inhibitory concentration of 27 0.91 ± 1.74 µM than astragalin 49.05 ± 1.49 µM whereas indomethacin has an IC 50 of 13.24 ± 2.20 µM. DM is a ubiquitous health disorder resulting from insulin deficiency or malfunction, which leads to a high rate of glucose in the blood (Kazeem et al, 2021). Research revealed that a high level of blood glucose enhances oxidative stress at the cell level, which boosts the pro-inflammatory cytokines activities, such as interleukins, tumor necrosis factors as well as mediators like nitric oxide.…”
Section: Potential Ligands Activities Validationsmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a chronic metabolic disease characterized by reduced insulin sensitivity or insulin deficiency, causing blood hyperglycemia in the postprandial and fasting state ( Kazeem et al, 2021 ). By 2045, it is projected that around 800 million of the global population will be hurt by this pandemic metabolic disorder with 6.7 million recorded deaths in 2021 ( Li et al, 2017 ; Ni et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%